Cross-sectional Study on Blood Pressure Control in the Department of Nephrology of the Escola Paulista de Medicina - UNIFESP - Freitas,João Batista de (2002)
OBJECTIVE - To assess hypertension control rates in a specialized university-affiliated medical department, the influence of sex, diabetes, and obesity on that control, and the strategies for the treatment of hypertension. METHODS - We carried out a cross-sectional study with 1,210 patients followed up for at least 6 months. Information was gathered from medical and nursing records and comprised the following data: sex, age, weight, height, abdominal and hip circumferences, blood pressure, and class and number of the antihypertensive drugs prescribed. To assess obesity, we used body mass index and waist/hip ratio. Blood pressure was considered under control when its levels were below 140/90 mmHg. RESULTS - The study consisted of 73% females and 27% males. Most females (31.7%) were 50 to 59 years of age, and most males (28.3%) were 60 to 69 years. The blood pressure control rate found was 20.9% for the 1,210 patients and 23.4% for the hypertensive diabetic patients (n=290). Despite the low control rates found, 70% of the patients used 1 or 2 antihypertensive medications. A high prevalence of obesity (38%) was observed, and females had a greater abdominal obesity index than males did (90% vs 82%, p<0.05). Patients with a greater body mass index had less control of blood pressure. CONCLUSION - The percentage of hypertensive patients with controlled blood pressure levels was low and was associated with a high prevalence of obesity. These data indicate the need for reviewing the strategies of global treatment for hypertension.